Minnesota symposia on child psychology [papers]. - University of Minnesota Institute of Child Development; Minnesota Symposia on Child Psychology (Minneapolis University of Minnesota Press, 1967)
Annual
Biological abstracts 0006-3169 1988-
Separately cataloged and classified in LC after v. 10.
Sponsored by the Institute of Child Development of the University of Minnesota.
Vol. 12- published: Hillsdale, N.J. : Erlbaum Associates, 1978-
Keywords: Child psychology -- Congresses